N‐cycling and balancing of the N‐deficit generated in the oxygen minimum zone over the Namibian shelf—An isotope‐based approach. Issue 1 (28th March 2013) - Nagel, Birgit; Emeis, Kay‐Christian; Flohr, Anita; Rixen, Tim; Schlarbaum, Tim; Mohrholz, Volker; van der Plas, Anja
Abstract: [1] The northern Benguela upwelling system is a nutrient‐replete region with high plankton biomass production and a seasonally changing oxygen minimum zone. Nitrate:phosphate ratios in fresh upwelling water are low due to denitrification in the near‐seafloor oxygen minimum zone and phosphate efflux from sediments. This makes the region a candidate for substantial dinitrogen fixation, for which evidence is scarce. Nutrient and oxygen data, N isotope data of nitrate, nitrogen isotope ratios of particulate matter, particulate organic carbon content, and suspended matter concentrations on a transect across the shelf and upper slope at 23°S illustrate N‐cycling processes and are the basis for estimating the contribution of N‐sources and N‐sinks to the reactive nitrogen pool. It appears that N‐removal due to denitrification exceeds N gain by N2 fixation and physical mixing processes by a factor of >6, although inorganic N:P ratios again increase as surface water is advected offshore. Nitrate and ammonium regeneration, nutrient assimilation with N:P < 16, shelf break mixing, atmospheric input, and N2 fixation all contribute to the restoration of inorganic N:P ratios back to Redfield conditions, but in seasonally changing proportions. The Benguela upwelling system thus is a nutrient source for the oceanic‐mixed layer where N‐sources and N‐sinks are not in balance and Redfield conditions can only re‐adjust by advection and mixing processes integrated over time. Key Points: Balancing of Nߚdeficit inherited from OMZ Interaction of waterߚmass mixture and Nߚcycling